BENCHMARKING OF RISK MANAGEMENT METHODS WITH REGARD TO VARIATIONS AS A SOURCE OF RISK. (May 2020) - Rapp, S.; Altner, M.; Albers, A.
Abstract: When developing new systems, there is always some kind of reference to existing systems. Various approaches aim at describing qualitatively different characteristics of such connections, often depicted as some form of variation. Among other things, this is done with regard to innovation potential and development risk. In this paper, we investigate the extent to which established methods of risk management refer to modelling approaches for variations by means as mentionend above. After a litertaure search 11 methods and method clusters are analyzed more in detail within a method benchmark.